FEATURES OF THE MANAGEMENT OF A COMORBID PATIENT WITH METABOLIC SYNDROME AND CHRONIC HEART FAILURE WITH REDUCED EJECTION FRACTION - Burdeyna, L.V.; Nazarova, M.S.; Kuzminova, N.V.; Lozinsky, S.E.; Shkarivsky, Y.L.; Firchuk, M.V.; Kniazkova, I.I. (World of Medicine and Biology, 2025)
Angiotensin-converting enzyme inhibitors or the combination of sacubitril and valsartan, beta-blockers, mineralocorticoid receptor antagonists, and sodium-dependent inhibitors of glucose-like cotransporter type 2 (SGLT2) are the standard of care for chronic heart failure with reduced ejection fraction (HFrEF). The implementation of an SGLT2 (Empagliflozin) in heart failure phenotype with reduced ejection fraction with/without type 2 diabetes and eGFR ≥ 20 mL/min/1.73 m2 is the result of the randomized, double-blind, placebo-controlled clinical trial EMPEROR-Reduced. Empagliflozin reduces the combined risk of death and hospitalization by 25 % and 30 % respectively, and slows the development of chronic renal failure in individuals with heart failure with reduced ejection fraction with/without type 2 diabetes. The presented clinical case corresponds to the results of the EMPEROR- Reduced clinical trial and shows that empagliflozin 10 mg/day in comorbid patients with the heart failure phenotype with reduced ejection fraction contributes not only to the improvement of left ventricular systolic function and quality of life, increased exercise tolerance and reduced frequency of hospitalizations, but also to the reduction of glycemia, normalization of blood lipid spectrum and indicators of nitrogen excretory renal function.